Dilemmas of Implementing Climate Change Adaptation Policies: The Prospects and Constraints of Multilevel Governance - Mongala, S.; Tema, K. S.; Mokoele, N. J.; Manamela, M. G. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
Globally, climate change has become a serious environmental problem within a development discourse. Most government structures have put in the initiatives to circumvent these harsh environmental realities without any success. This is due to the complexities surrounding climate change adaptation and mitigation. Literature provides pragmatic evidence that without collaboration between the governments, including public and private sectors, at the national and local level (i.e. Multi-Level Governance) mitigation of climate change will never be realised. Multilevel governance is based on the principles of collaboration, coordination and cooperation in implementing climate change adaptation. Thus, the multi-level principles can help in the promulgation and implementation of policies at both the national, local and global level that can be used as measures to adapt to climate change. The recent work on multi-level governance indicate that government are continuously challenged with the notion to merge different actors, either state or non- state to address climate change adaption which leaves a huge gap in most countries. Although, the adaption of multilevel governance may seem to have left some few important facts, but the approach tends to be more arguable in its positive effectiveness for addressing climate change. Multi-level governance approach may have some limitations and constraints when coming to the involvement of the local people but can still play a pivotal role as one of the climate change adaptation strategies. Theoretically, with literature based analysis, the paper reviewed Integrated Development Plans (IDPs) of selected municipalities within Capricorn District Municipality to uncover the level of integration and stakeholder engagement within local government in the quest to address climate change. The paper concludes that various local municipalities continue without proper plans, capacitated personnel and institutions for the implementation of climate change adaptation plans which derail the potentialities that multilevel governance holds in addressing urban challenges.
Article published in the 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Multilevel governance; Local government; Climate change; Integrated Development Plan; Climatic changes--South Africa--Limpopo; Urban climatology